Inclusive Ecotourism and Social Transformation in Bone Regency - Mega Erdawati; Andi Mudassir; Hazan Hazan; Nasaruddin Nasaruddin; Andi Wahyuni Syam (Universitas Medan Area, 2025)
This study aims to analyze the development strategies of inclusive ecotourism and its role in promoting social transformation and improving community welfare in Bone Regency, South Sulawesi. A qualitative case study design was applied, involving 20 informants comprising tourism entrepreneurs, village officials, community leaders, youth, and NGO representatives. Data were collected through semi-structured in-depth interviews (45–90 minutes each), participatory observation at tourist sites, and analysis of 12 policy and program documents. The data were analyzed thematically using Miles and Huberman’s framework, with triangulation of sources and member checking to ensure validity. The results indicate that inclusive ecotourism strategies rely on optimizing local natural and cultural potential (e.g., waterfalls, forests, traditional cuisine), governance through Pokdarwis and village cooperatives, and multi-stakeholder collaboration. These practices have led to income diversification—household earnings from tourism increased by an estimated 20–35%—strengthened cultural identity, and improved social cohesion measured through greater youth and women’s participation. The main challenges remain limited infrastructure, low tourism literacy, and internal conflicts due to unclear benefit-sharing mechanisms. On the other hand, opportunities include growing youth involvement (over 40% of active actors in new initiatives), government support programs, and integration with the regional tourism sector. The findings imply that inclusive, community-based ecotourism can serve as a sustainable development model when supported by policy interventions in infrastructure, capacity building, and equitable governance. This study contributes theoretically by linking ecotourism to social transformation and practically by offering policy recommendations for rural tourism development.